Characterization of the complete genome sequence of the recombinant norovirus GII.P16/GII.4_Sydney_2012 revealed in Russia - E. V. Zhirakovskaia; A. Y. Tikunov; S. N. Sokolov; B. I. Kravchuk; E. I. Krasnova; N. V. Tikunova (Вавиловский журнал генетики и селекции)
Noroviruses (the Caliciviridae family) are a common cause of acute gastroenteritis in all age groups. These small non-envelope viruses with a single-stranded (+)RNA genome are characterized by high genetic variability. Continuous changes in the genetic diversity of co-circulating noroviruses and the emergence of new recombinant variants are observed worldwide. Recently, new recombinant noroviruses with a novel GII.P16 polymerase associated with different capsid proteins VP1 were reported. As a part of the surveillance study of sporadic cases of acute gastroenteritis in Novosibirsk, a total of 46 clinical samples from children with diarrhea were screened in 2016. Norovirus was detected in six samples from hospitalized children by RT-PCR. The identified noroviruses were classified as recombinant variants GII.P21/GII.3, GII.Pe/GII.4_Sydney_2012, and GII.P16/GII.4_Sydney_2012 by sequencing of the ORF1/ORF2 junction. In Novosibirsk, the first appearance of the new recombinant genotype GII.P16/GII.4_Sydney_2012 was recorded in spring 2016. Before this study, only four complete genome sequences of the Russian GII.P16/GII.3 norovirus strains were available in the GenBank database. In this work, the complete genome sequence of the Russian strain Hu/GII.P16-GII.4/RUS/Novosibirsk/NS16-C38/2016 (GenBank KY210980) was determined. A comparison of the nucleotide and the deduced amino acid sequences showed a high homology of the Russian strain with GII.P16/GII.4_Sydney_2012 strains from other parts of the world. A comparative analysis showed that several unique substitutions occurred in the GII.P16 polymerase, N-terminal p48 protein, and minor capsid protein VP2 genes, while no unique changes in the capsid VP1 gene were observed. A functional significance of these changes suggests that a wide distribution of the strains with the novel GII.P16 polymerase may be associated both with several amino acid substitutions in the polymerase active center and with the insertion of glutamic acid or glycine in an N-terminal p48 protein that blocks the secretory immunity of intestinal epithelial cells. Further monitoring of genotypes will allow determining the distribution of norovirus recombinants with the polymerase GII.P16 in Russia.